Impact of growth-synthesis conditions on Cu2Zn1−xCdxSnS4 monograin material properties. (October 2016) - Nkwusi, G.; Leinemann, I.; Raudoja, J.; Mikli, V.; Karba, E.; Altosaar, M.
Abstract: This paper presents the impact of growth conditions on the properties of copper zinc cadmium tin sulfide (Cu2 Zn1−x Cdx SnS4 ) monograin powder synthesized in molten CdI2 . We studied the effects of synthesis time and flux amount on the properties of the monograin powder. Our results showed that we could control the phase composition, grain size and the morphology of the as grown Cu2 Zn1−x Cdx SnS4 powder by changing the synthesis conditions. We found that in comparison with other used fluxes (KI, NaI), monograin powders synthesized in molten CdI2 were less faceted and more round shaped. The average grain size increased as the flux amount decreased. The optimum synthesis time to obtain usable grain size with 50–100μ was found to be 160 h with CdI2 flux amount, providing the ratio of the volumes of CdI2 /CZTS is 0.5. Highlights: All the powders were Cu2 Zn1−x Cdx SnS4 solid solutions and the Cd content in synthesized powders was in the range of 1.9–4.8 at % with the used VCdI2/VCZTS ratios in between 0.5 and 5 at 650 °C. Optimum synthesis conditions were found at time 160 h at 650 °C with CdI2 flux concentration providing VCdI2 /VCZTS = 0.5. The grains produced with smaller flux concentrations and at higher temperature are less faceted and have more rounded shape. With increasing time as well as with increasing flux concentrations, faceted crystals became more obvious. The yield of usable powder grains with size of 50–100 μm was higher as the flux concentration decreased. The Cd incorporation into the crystals of the monograin powders was found to be dependent on the flux concentration but not on time.